The role of circRNA in breast cancer drug resistance - Yang,Shaofeng; Li,Donghai (PeerJ, 2024)
Among women with cancer, breast cancer has surpassed lung cancer to become the most prevalent type of cancer globally. High-throughput sequencing of breast cancer tissues from many patients has revealed significant variations in circRNA expression across different types of breast cancer. Chemotherapy is currently a very important method for treating breast cancer; however, as the number of chemotherapy sessions increases and considering factors such as the patient’s immune response, drug resistance has become a challenging issue in treating breast cancer. It is well known that drug resistance is associated with multiple factors, and different resistance mechanisms involve different roles of circRNA. This review consolidates literature from the past 5 years and addresses the shortcomings in the broad description of circRNA’s role in breast cancer drug resistance. It categorizes and describes the drug resistance and its mechanisms in different types of breast cancer, as well as the roles of circRNA and signaling pathways in drug resistance.
Keywords: BC; circRNA; Drug resistance; Antineoplastic